Open source solutions for knowledge management and technological ecosystems - García Peñalvo, Francisco José 1971-; Garcia-Holgado, Alicia 1986- (Advances in knowledge acquisition, transfer, and management (AKATM) book series, 2017)
"This book addresses the issues surrounding the search for each organization's unique data management needs, defining the tools necessary to fulfill them within their technological ecosystem, along with the selection, interoperability, and integration of these tools"--Provided by publisher